The effectiveness of Visit Malaysia Year 2007 campaign / Syahirah Shaari - Shaari, Syahirah (Faculty of Business and Management, 2007)
This research was conducted for the purposed to know the effectiveness of Visit Malaysia Year 2007 campaign and is it worth to be done or it is just a waste. Furthermore there is none of research or study being done regarding Visit Malaysia Year. The main objective of this research is to identify perception of public and tourists towards Visit Malaysia Year 2007 campaign whether it is effective or not after the third time Malaysia having Visit Malaysia Year. It is also wants to determine the best method in disseminating information of Visit Malaysia Year and what actually Malaysia attraction from public and tourists point of view. Beside that this study also wants to identify what events actually capture much interest among the respondents. In this study the researcher using AIDA model as the theoretical framework. The objective and also the questionnaire designed based on this framework. The respondent of this study was public and tourists in Mid Valley and KL Sentral. 62 questionnaires have been distributed to them. The researcher had used judgement sampling as the sampling technique. In analyzing the data the researcher used SPSS Version 15 to get the frequency table and also cross tabulation from those table and chart the researcher interpret and getting the conclusion and also recommendation. The conclusion of this study is the outcome from the survey analysis and findings based on the questionnaire. Through the research, it shows the effectiveness of Visit Malaysia Year 2007 from respondents view. It's considered that Visit Malaysia Year 2007 is effective and should be continue. But there is still a lot of effort can be done to improve Visit Malaysia Year in the future and the strategy being deliver in the recommendation section by the researcher.